Living different lives: Early social differentiation identified through linking mortuary and isotopic variability in Late Neolithic/ Early Chalcolithic north-central Spain - Fernández-Crespo, T; Schulting, R (Public Library of Science, 2017)
Variation in burial location and treatment is often observed in the prehistoric archaeological record, but its interpretation is usually highly ambiguous. Biomolecular approaches provide the means of addressing this variability in a way not previously possible, linking the lives of individuals to their funerary treatment. Here, we undertake stable carbon and nitrogen isotope analyses on a substantial sample of 166 individuals from a series of broadly contemporary Late Neolithic/ Early Chalcolithic (3500 to 2900 cal BC) mortuary monuments (El Sotillo, Alto de la Huesera, Chabola de la Hechicera and Longar) and caves (Las Yurdinas II, Los Husos I and Peña Larga) within a very spatially restricted area of north-central Spain, with sites separated by no more than 10 km on average. This spatial and temporal proximity allows us to focus on the question at the appropriate scale of analysis, avoiding confounding variables such as environmental change, diachronic trends in the subsistence economy, etc. The results demonstrate a statistically significant difference in human δ13C values between those interred in caves and those placed in monuments. The difference appears to be correlated with fine-grained environmental factors (elevation/ temperature/ precipitation), suggesting that use of the landscape was being divided at a very local scale. The reasons for this partitioning may involve differential social status (e.g. those interred in caves may be of lower standing with more restricted access to the valley's arable resources) or economic specialization (e.g. upland herding vs. valley farming) within the same community or, alternatively, different populations performing different funerary practices and following distinct subsistence economies in some respect. Our results contribute to a better understanding of the development of social differentiation and community specialisation on the scale of the immediate lived landscape.